"Asian yuppies…are always looking for something new and different": creating a tobacco culture among young Asians. (24th November 2004) - Knight, J; Chapman, S
Abstract : Objective: To identify and analyse the themes employed by the Asian based transnational tobacco companies to construct a tobacco culture among Asian young men and women. Methods: Systematic review of relevant tobacco industry documents made public through the Master Settlement Agreement. Results: The industry utilised six vehicles and themes to construct a tobacco culture in Asia: music, entertainment (including nightclubs, discos, and movies), adventure, sport (including motorsports, soccer, and tennis), glamour (beauty and fashion), and independence. Conclusions: The tobacco industry set about constructing a tobacco culture that sought to make smoking desirable, even normal, for young men and women. Understanding the way industry constructed this culture provides insights into ways that culture might now be challenged. Countering the transnational nature of many activities will require coordinated effort at the international, regional, and national levels. Implementation of the Framework Convention on Tobacco Control (FCTC) will be a powerful tool in this process. All nations throughout Asia are encouraged to support the FCTC and its broad protocols addressing advertising and sponsorship. Measures are also required to disassociate smoking from progress in sex equality.